1994
DOI: 10.1063/1.110990
|View full text |Cite
|
Sign up to set email alerts
|

Atomic hydrogen-induced interface degradation of reoxidized-nitrided silicon dioxide on silicon

Abstract: Remote hydrogen plasma exposure is used to study the transport of atomic hydrogen, H0, through reoxidized-nitrided oxides and SiO2 and to quantify H0-induced degradation of their interfaces with silicon. It is directly demonstrated that (1) H0 is extremely reactive and produces large numbers of interface states; (2) the transport of H0 to the silicon/oxide interface is strongly suppressed in reoxidized-nitrided oxides; and (3) this suppression of the H0 transport is mainly responsible for the much slower inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(35 citation statements)
references
References 19 publications
1
34
0
Order By: Relevance
“…Figure 5͑b͒ schematically shows the diffusion of released hydrogen into the bulk of gate oxide. Although these diffused hydrogen can induce dielectric degradations, nitride layer located away from the interface slows down the diffusion of released hydrogen atoms, 21,22 resulting in the reduction in the dielectric degradation. Also, this proposition is corroborated by the observation shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 5͑b͒ schematically shows the diffusion of released hydrogen into the bulk of gate oxide. Although these diffused hydrogen can induce dielectric degradations, nitride layer located away from the interface slows down the diffusion of released hydrogen atoms, 21,22 resulting in the reduction in the dielectric degradation. Also, this proposition is corroborated by the observation shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was shown that the diffusion of hydrogen is slowed down by nitride layer containing small nitrogen ͑2%-4%͒ in gate oxide, resulting in the reduction in charge generation. 21,22 Thus, we propose that the trap charge generation caused by diffused hydrogen is reduced by the presence of nitrided layer, which has proper amount of nitrogen and locates away from the interface as for the TMN sample with F N/O =2.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike low temperature forming gas anneals where hydrogen is in molecular form, hydrogen in an Ar + H 2 based plasma is mostly in ionized states including ions where it is bonded with oxygen, such as H 3 O + and H 2 O + [14,15]. It is conceivable that these chemically active ions [16] react with the silicon substrate, oxidising it and creating an interfacial layer of silicon oxide.…”
Section: Ftir Measurementsmentioning
confidence: 96%
“…A possible way to minimize (even to prevent) the growth of SiO 2 -containing interfacial layer is a slight nitridation of Si before deposition of Ta 2 O 5 resulting to formation in fact of SiO x N y at the Si instead of SiO 2 [22][23][24]. SiO x N y is not only with higher k than SiO 2 , but it is expected to improve the reliability and immunity of the stack capacitor to hot electron degradation [25,26]. Among a number of methods for Si surface nitridation we used N-implantation in this work.…”
Section: Introductionmentioning
confidence: 98%